2018
DOI: 10.1016/s2352-3026(18)30039-5
|View full text |Cite
|
Sign up to set email alerts
|

CHOP versus GEM-P in previously untreated patients with peripheral T-cell lymphoma (CHEMO-T): a phase 2, multicentre, randomised, open-label trial

Abstract: SummaryBackgroundOutcomes with CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisolone) or CHOP-like chemotherapy in peripheral T-cell lymphoma are poor. We investigated whether the regimen of gemcitabine, cisplatin, and methylprednisolone (GEM-P) was superior to CHOP as front-line therapy in previously untreated patients.MethodsWe did a phase 2, parallel-group, multicentre, open-label randomised trial in 47 hospitals: 46 in the UK and one in Australia. Participants were patients aged 18 years and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 30 publications
(53 reference statements)
0
42
0
3
Order By: Relevance
“…The optimal regimen for PTCL has yet to be determined, but most centers consider anthracycline-based regimens, mostly CHOP, for nodal PTCLs. 46 There are some questions if the addition of etoposide to CHOP could improve the outcome of patients with nodal PTCL, albeit at a higher hematological toxicity. 47 More intensive regimens have failed in improving responses in PTCL.…”
Section: Peripheral T-cell Lymphomasmentioning
confidence: 99%
“…The optimal regimen for PTCL has yet to be determined, but most centers consider anthracycline-based regimens, mostly CHOP, for nodal PTCLs. 46 There are some questions if the addition of etoposide to CHOP could improve the outcome of patients with nodal PTCL, albeit at a higher hematological toxicity. 47 More intensive regimens have failed in improving responses in PTCL.…”
Section: Peripheral T-cell Lymphomasmentioning
confidence: 99%
“…[4] Due to their extreme toxicity, bifunctional alkylating agents were initially developed as chemical weapons and later,c ertain derivatives were recognized as having important chemotherapeutic activities. [5] Some of these agents are still widely used in the first line therapies of various lymphomas, [6] leukemias, [7] and solid tumors. [8] Thelow chemoselectivity of these drugs contributes to their undesirable side effects, [9] and their promiscuity makes it difficult to ascertain their exact mode of action.…”
mentioning
confidence: 99%
“…Gemcitabine-based regimens also failed to show advantage over standard CHOP regimen. In a phase 2 multicentre randomized trial, the CR rate of GEM-P regimen (gemcitabine, cisplatin, and methylprednisolone) was inferior to CHOP regimen (46% vs. 62%), with 2-year PFS rates of 38% versus 37%, respectively [9]. The above studies suggested that the past usage of cytotoxic chemotherapy at varying intensity was not su cient in the treatment of PTCL.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of etoposide to CHOP (CHOEP) might improve response rate and event-free survival (EFS) for younger patients (aged ≤ 60 years) [7,8]. Non-anthracycline based regimens such as gemcitabine-based chemotherapy were explored in several studies for PTCL patients but still showed non-superior results compared to CHOP-like chemotherapy [9]. At our center, Zhang Y et al conducted a phase 2 study of GDP-ML regimen (combined gemcitabine, cisplatin, dexamethasone, methotrexate, and pegaspargase) in patients with newly diagnosed PTCLs, which showed an ORR of 55.4% and 2-year OS rate of 38.2% (registered with www.…”
Section: Introductionmentioning
confidence: 99%